Redescription of Ochmacanthus batrachostoma (Miranda-Ribeiro, 1912) (Siluriformes: Trichomycteridae): a possible case of incipient paedomorphism - Caio S. Neto; Mário de Pinna (Neotropical Ichthyology)
ABSTRACT The lepidophagous stegophiline catfish Ochmacanthus batrachostoma (Miranda-Ribeiro, 1912) is endemic to the Paraná-Paraguai basin and is the only member of its genus in that drainage. It remains a poorly-known taxon mainly due to the historical scarcity of study specimens. The species is herein redescribed on the basis of type and non-type specimens from Brazil, Argentina and Paraguay. Ochmacanthus batrachostoma can be distinguished from congeners by the presence of long maxillary and rictal barbels, reduction of the posterior end of the caudal peduncle, a tadpole-like caudal fin and peduncle, among other morphometric traits and features of internal anatomy. Comparisons show that a number of unique traits of adult O. batrachostoma resemble conditions seen in juvenile specimens of other members of Stegophilinae. Such traits are also more pronounced in juveniles of O. batrachostoma itself. The species also has the smallest maximum body size in Ochmacanthus and among the smallest of any stegophiline. In combination, such observations suggest that the species is paedomorphic, although to a degree less extreme than seen in some other trichomycterids. This is the first possible case of paedomorphosis identified for stegophilines.